Combined dermal autograft in the surgical treatment of full thickness burns - L. P. Loginov; S. V. Smirnov (Трансплантология (Москва))
The authors developed the method of skin grafting using a combined (epidermis-dermis) autograft that allows increasing the skin graft area two-fold or even more. We have assessed the survival of the dermal component of the graft in 10 patients who sustained full thickness burns of 5 - 15 %of the total body surface area (TBSA). We have demonstrated that the most complete survival of the dermal coinponent of the skin graft was observed in the cases of postoperative using the dressings containing epidermal growth factor (Hebermin ointment) and moisture- retaining film bandages (native-manufactured Breiemenderm film bandage). The period till the final epithelialization of the dermal component and donor wound made 2.5 - 3 weeks after grafting procedure. We hope that this period may be considerably shortened thanks to applying cellular technology and tissue engineering achievements in postoperative period. Improved results obtained in the survival of the dermal component of the combined skin graft allow using it to solve the problem of deficient donor skin resources in the patients with severe extensive burns.